Some properties of elementary particles or a determination of the lifetime of the neutral pi meson - Evans, D (1963)
Theoretical estimates of the lifetime of the neutral π meson have indicated a value of the order of 10−17 secs. In order to determine the lifetime by flight distance measurements a method employing very fine resolution is required. Nuclear emulsions provide a medium for resolution of distances of the order of a micron. This experiment uses the same principle as that first tried by Harris et al.(1957). The decay at rest of the K+ meson in the Kπ2 mode (π+π0) provides a π0 of unique velocity and a direction directly opposite to that of the π+; the latter being charged, leaves a track in the emulsion. The decay of the π0 is detected in emulsion if it takes place in the Dalitz mode:- π0 γ+e++e− (br. ratio 1.2%) Detection is possible because of the emission of charged particles. A stack of Ilford L4 emulsions was exposed to a beam of stopping K mesons. After processing, the stack was scanned for Kπ2 decays with the emission of a Dalitz pair. Other π0 producing decays of the K+ (Kμ3, Ke3, τ′) were at first indistinguishable from the desired Kπ2 decays. In order to reduce this contamination, grain density measurements were made on the charged secondary from the K+ decay. By rejecting events in which g* was greater than 1.3 all τ′ and 30% of the Kμ3 events were rejected. A correction factor was calculated to account for the remaining decays. The co-ordinates of the grains composing the events were measured relative to axes fixed in the field of view. A bifilar micrometer eyepiece was used which has the motions of the cross-wires digitised to enable rapid measurement. The co-ordinates were automatically punched out on to tape ready for input to the computer. The tracks of the particles were obtained by fitting straight lines to the measured co-ordinates. The decay point of the π0 was defined as the intersection of the electron tracks with the line of flight of the π+. The point of production was taken as the foot of the perpendicular from the measured position of the K+ on to the π+ trajectory. The effects of errors due to measurement, "grain noise" and grain size were thoroughly investigated. Use was made of co-ordinate measurements on τ decays of the K+ (π+π+π−) where it is known that the three tracks converge on the point of decay of the K+. An estimation of the lifetime was made using a likelihood calculation. It was discovered that the presence of events giving anomalous flight distances affected the estimate considerably. A suitable cutoff criterion was applied to reject these events. The result after allowing for the effect of contamination events referred to earlier was:- τπ0 = (1.56 + 0.55 ) × 10−16 secs. − 0.45